Cyberbullying Victimization and Suicide Attempt Among Adolescents: A Cross-National Comparison - Grimland, Meytal; Mori, Yuko; Lesinskiene, Sigita; Li, Liping; Ong, Say How; Praharaj, Samir Kumar; Wiguna, Tjhin; Zamani, Zahra; Heinonen, Emmi; Gilbert, Sonja; Brunstein, Klomek Anat; Sourander, Andre; et al. (MDPI AG, 2025)
The widespread use of the Internet among teenagers has raised concerns about cyberbullying and its impact on adolescent well-being. This study examined the association between cyberbullying victimization and suicide attempts among adolescents in high-income and low/middle-income countries. Data from six countries (Singapore, China, Iran, Indonesia, India, and Lithuania) were collected as part of the Eurasian Child Mental Health Study. A total sample of 9892 adolescents aged 13–15 years old (51.9% girls) was analyzed. Generalized estimating equation models with school-wise clusters were conducted. The prevalence of suicide attempts was 4.8%, with higher rates among girls. Cyberbullying victimization only was reported by 5.4% of the participants, while traditional bullying victimization only was reported by 19.2%. The study found that being a victim of combined (both traditional and cyberbullying) had the highest odds of suicide attempt in both high-income and low/middle-income countries. Emotional symptoms were identified as a moderator, influencing the association between combined bullying victimization and suicide attempt. These findings highlight the urgent need for global efforts to prevent and intervene in cyberbullying and its detrimental effects on adolescent mental health. The study emphasizes the importance of examining regional risk factors and implementing targeted interventions to address this growing public health concern.